1998
DOI: 10.1046/j.1365-246x.1998.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day variability of geomagnetic hourly amplitudes at low latitudes

Abstract: A study of the variability of the amplitude of Sq at a fixed hour from one day to the next at nine stations from the dip equator to about 22° north of it has produced interesting results. The amplitude and sign of the variability change virtually randomly, making the mean practically zero. The variability occurs at all hours of the day. Its magnitudes in the components D, H and Z have the same diurnal variation, which peaks in the noon period like Sq(H) in low latitudes, and a weak seasonal variation that peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 92 publications
2
15
0
Order By: Relevance
“…They found small correlation coefficient values between the EEJ and Sq when the calculations were performed during five quiet days of each month in 1998. Their results are in agreement with work of Okeke et al (1998), which used data in the Indian sector during the quiet year of 1986. Conversely, a study by Ogbuehi et al (1967) showed that the correlation coefficient between EEJ and Sq reached −0.6 during the December solstice in 1958.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They found small correlation coefficient values between the EEJ and Sq when the calculations were performed during five quiet days of each month in 1998. Their results are in agreement with work of Okeke et al (1998), which used data in the Indian sector during the quiet year of 1986. Conversely, a study by Ogbuehi et al (1967) showed that the correlation coefficient between EEJ and Sq reached −0.6 during the December solstice in 1958.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies have used the two-station method to calculate the EEJ as the difference between measurements taken at a dip equator station and at an off-dip equator station, and data from the off-dip equator station are typically used directly to represent the global Sq contribution at the dip equator. In many cases, no significant correlation is obtained as shown in Ogbuehi et al (1967), Okeke et al (1998), and Okeke and Hamano (2000). In contrast, studies by Kane (1971) and Yamazaki et al (2010), which used the total H component at the dip equator to represent the EEJ (which we hereafter refer to as the total current), revealed a good correlation with Sq at off-dip equator stations.…”
Section: Introductionmentioning
confidence: 95%
“…Okeke et al (1998), from the results of their work carried out with Indian stations, found out that the variability of D component at Annamalainagar has a considerable part due to the EEJ fields as in the case of H and Z at this station, which suggested the existence of EEJ D field. Figures 2 and 3 show the variations in the three components in the months of June and October respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Forbush and Casaverde (1961) studied the features of EEJ in D H and Z across the dip equator, and assumed that EEJ produced none or very negligible D field. However, recent work of Rastogi (1996), Onwumechili (1997) and Okeke et al (1998) have shown that D field of EEJ does exist. Patil et al (1983), described the mean daily variations of different components of the geomagnetic field, declination…”
Section: Introductionmentioning
confidence: 98%
“…He observed that universal time (UT) variability are made up of two parts; the regular variations during quiet period (Sq) and the occasional variation during very disturbed period (irregular known as , Maeda (1968)). Mitra (1947);Schlapps (1968);Onwumechilli and Ogbuechi (1962); Rabiu (1996Rabiu ( , 2002; Okeke and Rabiu (1998) have investigated Sq day-to-day variations at low and middle latitudes during very quiet period. Irrespective of latitudinal differences, Mitra (1947); Rabiu (1996Rabiu ( , 2002; Okeke and Rabiu (1998) observed higher magnitudes of Sq of H during daytime period (0600-1800 local time, LT) compare to the nighttime hours (1900-0500 LT).…”
Section: Introductionmentioning
confidence: 99%